Upper motor neuron dysfunction is associated with the presence of behavioural impairment in patients with amyotrophic lateral sclerosis. (18th January 2022) - Maranzano, Alessio; Poletti, Barbara; Solca, Federica; Torre, Silvia; Colombo, Eleonora; Faré, Matteo; Ferrucci, Roberta; Carelli, Laura; Verde, Federico; Morelli, Claudia; Silani, Vincenzo; Ticozzi, Nicola
Abstract: Background and purpose: Increasing evidence shows that approximately half of patients with amyotrophic lateral sclerosis (ALS) display cognitive (ALSci) or behavioural (ALSbi) impairment, or both (ALScbi). The aim of our study was to assess whether the burden of upper and lower motor neuron involvement is associated with the presence of cognitive and behavioural impairment. Methods: A single‐centre retrospective cohort of 110 Italian ALS patients was evaluated to assess correlations between motor and cognitive/behavioural phenotypes. Upper motor neuron regional involvement was measured with the Penn Upper Motor Neuron Score (PUMNS), whilst lower motor neuron signs were assessed using the Lower Motor Neuron Score. The Edinburgh Cognitive and Behavioural ALS Screen—Italian version and the Frontal Behaviour Inventory were administered to evaluate patients' cognitive and behavioural profiles. Results: The PUMNS at first visit was significantly higher in behaviourally impaired ALS patients (ALSbi and ALScbi) compared to behaviourally unimpaired individuals (ALS and ALSci) (9.9 vs. 6.9, p = 0.014). Concerning the different Frontal Behaviour Inventory subdomains, higher PUMNS correlated with the presence of apathy, emotive indifference, inflexibility, inattention, perseveration and aggressiveness. Conclusion: To our knowledge, this is the first study showing that a clinical prominent upper motor neuron dysfunction is associated with a more significant behavioural impairment in ALS patients, suggesting the hypothesis of a preferential spreading of the pathology from the motor cortex to the ventromedial prefrontal and orbitofrontal cortex in this group of patients. Abstract : An inpatient cohort of 110 Italian patients diagnosed with amyotrophic lateral sclerosis and other motor neuron diseases was evaluated to assess a correlation between motor phenotype and cognitive or behavioural impairment. The Penn Upper Motor Neuron Score at first visit was significantly higher in behaviourally impaired amyotrophic lateral sclerosis patients compared to behaviourally unimpaired individuals (9.90 vs. 6.97, p = 0.014). This association seems to confirm the hypothesis of a preferential spreading of the pathology from the motor cortex to the ventromedial prefrontal and orbitofrontal cortex in this group of patients.